2017
DOI: 10.1016/j.neuroimage.2017.07.059
|View full text |Cite
|
Sign up to set email alerts
|

Predicting brain age with deep learning from raw imaging data results in a reliable and heritable biomarker

Abstract: Machine learning analysis of neuroimaging data can accurately predict chronological age in healthy people and deviations from healthy brain ageing have been associated with cognitive impairment and disease. Here we sought to further establish the credentials of 'brainpredicted age' as a biomarker of individual differences in the brain ageing process, using a predictive modelling approach based on deep learning, and specifically convolutional neural networks (CNN), and applied to both pre-processed and raw T1-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
694
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 721 publications
(743 citation statements)
references
References 62 publications
44
694
5
Order By: Relevance
“…Overall, age prediction error was in range with previous "brain age" estimates (Ball, Adamson, et al, 2017;Cole et al, 2017;Franke, Luders, May, Wilke, & Gaser, 2012) confirming that utility of NMF for providing useful low-rank representations of large imaging data sets (Varikuti et al, 2018). We performed NMF using five different levels: 2, 5, 10, 15, and 20 and compared how well the resulting components could reconstruct the original data, and how well the resulting timecourses could be used to predict chronological age.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Overall, age prediction error was in range with previous "brain age" estimates (Ball, Adamson, et al, 2017;Cole et al, 2017;Franke, Luders, May, Wilke, & Gaser, 2012) confirming that utility of NMF for providing useful low-rank representations of large imaging data sets (Varikuti et al, 2018). We performed NMF using five different levels: 2, 5, 10, 15, and 20 and compared how well the resulting components could reconstruct the original data, and how well the resulting timecourses could be used to predict chronological age.…”
Section: Discussionsupporting
confidence: 65%
“…We used Gaussian process regression implemented in scikit-learn (v0.20.0) to estimate age for each subject based on their individual component weights within a 10-fold cross-validation framework (Cole et al, 2017). We used Gaussian process regression implemented in scikit-learn (v0.20.0) to estimate age for each subject based on their individual component weights within a 10-fold cross-validation framework (Cole et al, 2017).…”
Section: Reconstruction Error Cross-validation and Age Predictionmentioning
confidence: 99%
“…It is important to remark that the value of MAE of BCA equal to 5.89 years is no better than the performance of some other prediction models using merely volumetric data (Cole, Poudel, et al, 2017;Mwangi et al, 2015). Next, the significant features are pooled to create an optimized linear regression model capable to assess the biological brain age of a given connectome with minimal error.…”
Section: Network Homeostasis: Increased Fc In Combination With Decrmentioning
confidence: 99%
“…With recent advances in deep learning, DNNs are expected to improve prediction performance (Cole & Franke, ). However, most studies showed DNN yielded similar prediction performance to traditional ML methods (Aycheh et al, ; Cole et al, ). For example, a convolutional neural network (CNN) achieved comparable prediction accuracy ( r = .96) to GPR (Cole et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies showed DNN yielded similar prediction performance to traditional ML methods (Aycheh et al, ; Cole et al, ). For example, a convolutional neural network (CNN) achieved comparable prediction accuracy ( r = .96) to GPR (Cole et al, ). Though prediction performance was not significantly improved, one advantage is that DNN is directly applicable to raw imaging data.…”
Section: Introductionmentioning
confidence: 99%